Manifestações do público receptor sobre ações de responsabilidade sociocomunicacional: um estudo de caso a partir das comunidades do projeto criança esperança no orkut - Souza, Alessandro Souza de (Universidade do Vale do Rio do Sinos, 2009)
This dissertation discusses the idiosyncrasies of manifestations, on digital environments, about corporate strategies for reinforcement of institutional image, specially Social Responsibility Actions. To that end, it starts with a discussion of the centrality of businesses in contemporary social dynamics and proposes the concept of “Sociocomunicational Responsibility” to describe the specifics of social appealling corporate actions. Critical readings of such dynamics were observed on the internet, as in this environment individuals spontaneously register their impressions. The case studied was Rede Globo’s Projeto Criança Esperança, more specifically its discussion in thematic communities encountered in the social network service Orkut. Findings suggest the importance of spontaneously generated online data for reception studies. The case chosen led to the identification of (positive and negative) public criticism, as well as the perception, by the public, of a causal chain culminating on an institutional ans
Keywords: imagem institucional; internet; orkut; responsabilidade sociocomunicacional; recepção; corporate image; internet; orkut; sociocomunicational responsibility; reception; Ciências Sociais Aplicadas